2017
DOI: 10.3390/cancers9080104
|View full text |Cite
|
Sign up to set email alerts
|

Complex Determinants of Epithelial: Mesenchymal Phenotypic Plasticity in Ovarian Cancer

Abstract: Unlike most epithelial malignancies which metastasize hematogenously, metastasis of epithelial ovarian cancer (EOC) occurs primarily via transcoelomic dissemination, characterized by exfoliation of cells from the primary tumor, avoidance of detachment-induced cell death (anoikis), movement throughout the peritoneal cavity as individual cells and multi-cellular aggregates (MCAs), adhesion to and disruption of the mesothelial lining of the peritoneum, and submesothelial matrix anchoring and proliferation to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 267 publications
(313 reference statements)
2
82
1
4
Order By: Relevance
“…[119][120][121] EMT is an important part of ovarian cancer progression, in which free floating spheroids attach to the mesothelium, disseminate and metastasize to surrounding tissues. 122,123 Expression of CD44 and CA125, high levels of IL-6, CXR4, and CXCL12 and the amplification of PIK3CA, Akt and bone morphogenetic protein (BMP) pathways have been associated with ovarian cancer EMT. 17,124,125 The review by Tan et al provides an in-depth look at epithelial ovarian cancer metastasis.…”
Section: Relating In Vitro Mechanotransduction Results To In Vivmentioning
confidence: 99%
“…[119][120][121] EMT is an important part of ovarian cancer progression, in which free floating spheroids attach to the mesothelium, disseminate and metastasize to surrounding tissues. 122,123 Expression of CD44 and CA125, high levels of IL-6, CXR4, and CXCL12 and the amplification of PIK3CA, Akt and bone morphogenetic protein (BMP) pathways have been associated with ovarian cancer EMT. 17,124,125 The review by Tan et al provides an in-depth look at epithelial ovarian cancer metastasis.…”
Section: Relating In Vitro Mechanotransduction Results To In Vivmentioning
confidence: 99%
“…Stemmer et al showed that Snail could stimulate the activity of Wnt pathway by down‐regulation of E‐cadherin leading to the release of β‐catenin and increase of cytoplasmic β‐catenin . The shedding of E‐cadherin ectodomain induced epithelial ovarian cancer cells detaching from tumor surface and disseminating into the peritoneal cavity, destroyed existing cell junction between epithelial ovarian cancer cells, and promoted cancer cell invasion by triggering the up‐regulation of MMP‐2 and MMP‐9 expression …”
Section: Discussionmentioning
confidence: 99%
“…EMT programs generally occur in physiological conditions, such as during implantation, embryogenesis, and organ development (type‐1 EMT) and in pathological settings, including tissue regeneration and fibrosis (type‐2 EMT) as well as cancer progression and metastasis (type‐3 EMT) . EMT plays a crucial role in peritoneal dissemination of ovarian carcinoma, which is characterized by detachment from the primary tumor, movement into the peritoneal cavity as single cells and multi‐cellular aggregates (MCAs) surviving and traveling with intra‐abdominal fluid, adhesion to peritoneal tissues and invasion through the mesothelial lining of the peritoneum, followed by anchoring to submesothelial matrix and generating secondary lesions in new distant metastatic organs mediated by mesenchymal‐to‐epithelial transition (MET) …”
Section: Introductionmentioning
confidence: 99%
“…Malignant cells are shed from the primary tumor into the peritoneal cavity survive as free‐floating single cells or spheroids in the “malignant ascitic fluid” that is encountered in the majority of patients with OvCa . Single cells and spheroids can survive anchorage‐independent apoptosis “anoikis,” proliferate in suspension and seed onto the mesothelial lining of the peritoneal cavity, resulting in extensive peritoneal dissemination . Malignant cells isolated from ascitic fluid exhibit dual “hybrid” as well as heterogeneous E‐and N‐Cadherin expression .…”
Section: Introductionmentioning
confidence: 99%
“…Single cells and spheroids can survive anchorage‐independent apoptosis “anoikis,” proliferate in suspension and seed onto the mesothelial lining of the peritoneal cavity, resulting in extensive peritoneal dissemination . Malignant cells isolated from ascitic fluid exhibit dual “hybrid” as well as heterogeneous E‐and N‐Cadherin expression . This cadherin‐plasticity influences cell‐cell interactions, spheroid formation, and is implicated in the dynamic switch between epithelial‐mesenchymal transition (EMT) and mesenchymal‐epithelial transition (MET).…”
Section: Introductionmentioning
confidence: 99%